Hubungan antara Tingkat Pendapatan Keluarga dan Pola Konsumsi Pangan Masyarakat: Sebuah Literatur Review - Kartikasari, Dewi; Yuliana, Yuliana; Yulastri, Asmar (Lembaga Yasin AlSys, 2024)
Food is a basic need that must be fulfilled before other needs, such as clothing, shelter, and education. This study aims to analyze the impact of family income on the food consumption patterns of society, specifically how income affects access to and the quality of food consumption. Through a literature review, this study examines various previous studies on the factors influencing food consumption patterns. The findings show that family income significantly affects food consumption patterns. Families with higher income tend to consume more nutritious and diverse food, while low-income families are more limited in choosing nutritious food, which may negatively impact their health. These findings highlight the importance of income increase in improving food consumption patterns. This study also aims to provide strategic recommendations for improving access to quality food for low-income families. By integrating previous findings, this research is expected to serve as a reference for policymakers in developing programs that support food security and the improvement of the nutritional quality of society, contributing to the future welfare development of the community.